1993
DOI: 10.1002/j.1460-2075.1993.tb05952.x
|View full text |Cite
|
Sign up to set email alerts
|

One member of a gro-ESL-like chaperonin multigene family in Bradyrhizobium japonicum is co-regulated with symbiotic nitrogen fixation genes.

Abstract: This report is concerned with the structural characterization and genetic regulation of new bacterial groES and groEL chaperonin genes, and presents two novelties. The first is the discovery that the nitrogen fixing soybean root nodule bacterium, Bradyrhizobium japonicum, unlike all other prokaryotes investigated so far, possesses a multigene family consisting of five very similar, though not identical, groESL‐like genes. The second novelty relates to the finding that these five homologues are expressed to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 84 publications
(41 reference statements)
7
137
0
2
Order By: Relevance
“…Upon heat shock, HrcA is destabilized, released from the CIRCE element, allowing the production of heat-shock proteins, which in turn attend to the cellular stressed proteins till normalcy is resumed. Upon recommencement of normalcy, GroEL, free from cellular stressed proteins, facilitates the folding and assembly of HrcA and the repression of the downstream genes of groEL genes (Kong et al 1993;Fischer et al 1993;Karunakaran et al 2003;Barreiro et al 2005). The existence of multiple groEL genes opens up several hypotheses on their function and evolution and on the distribution of the substrates.…”
Section: Multiple Groels In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Upon heat shock, HrcA is destabilized, released from the CIRCE element, allowing the production of heat-shock proteins, which in turn attend to the cellular stressed proteins till normalcy is resumed. Upon recommencement of normalcy, GroEL, free from cellular stressed proteins, facilitates the folding and assembly of HrcA and the repression of the downstream genes of groEL genes (Kong et al 1993;Fischer et al 1993;Karunakaran et al 2003;Barreiro et al 2005). The existence of multiple groEL genes opens up several hypotheses on their function and evolution and on the distribution of the substrates.…”
Section: Multiple Groels In Bacteriamentioning
confidence: 99%
“…These bacteria offer an interesting picture for multiple chaperonin genes (Rusanganwa and Gupta 1993;Wallington and Lund 1994), boasting the highest number of chaperonin genes among bacteria. Bradyrhizobium japonicum hosts seven groEL genes with five of them in operonic arrangement with groES homologues (Fischer et al 1993;Kaneko et al 2000Kaneko et al , 2002, and at least one of the multiple GroELs has been dedicated for folding proteins involved in nitrogen fixation. Interestingly, several non-rhizobial nitrogen-fixing bacteria bear three to four copies of chaperonin genes (Moulin et al 2001;Normand et al 2007), while non-nitrogen-fixing rhizobia have only one copy (Wood et al 2001), suggesting a correlation between the presence of multiple chaperonins and nitrogen fixation pathway.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
“…Different copies of groELs might have diverged sequentially in a later event to attain the ability to function under different conditions of stress. Indeed it has been reported that in B. japonicum expression of the groEL5 gene is regulated by cellular oxygen and that of groEL3 is regulated by the nitrogen fixation system (Fischer et al 1993). However, inferences regarding the chain of evolutionary events within the rhizobial clade cannot be drawn due to weak statistical support.…”
Section: Evolutionary Analysis Of Multiple Groelsmentioning
confidence: 99%
“…Unfortunately, commercially available E. coli GroES antibodies showed extensive nonspecific crossreactivity with these solutions and were therefore not helpful in this regard. Since the early 1990s, when GroEL research was in its infancy, several reports have appeared suggesting that GroEL might have something to do with nitrogenase regulation and assembly (40)(41)(42)(43)(44). For example, 35 S pulse-chase experiments with Klebsiella pneumoniae suggested transient binding of newly synthesized Fe protein and MoFe protein polypeptides to GroEL.…”
Section: Resultsmentioning
confidence: 99%